SEVERE HYPERSENSITIVITY TO ANTIEPILEPTIC DRUGS: BRITISH NEUROLOGICAL SURVEILLANCE UNIT (BNSU). Issue 11 (9th October 2013) - Yip, Vincent; Heslop, S; Pennington, C; Evely, J; Marson, AG
Abstract : Hypersensitivity reactions account for 2–6% of all hospital admissions. Severe hypersensitivity reactions such as hypersensitivity syndrome (HSS), acute generalised exanthematous pustulosis (AGEP), Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are associated with significant mortality and long–term morbidity including scarring and blindness. These hypersensitivity reactions are comparatively common with antiepileptic drug (AED) therapy. The incidence of HSS is approximately 1 in 500 AED exposures whilst SJS/TEN is estimated to occur in 1 in 5000 exposures to carbamazepine (CBZ). More recently, research has demonstrated that susceptibility to certain AED–induced hypersensitivity reactions are strongly associated with genetic risk factors. For example, carriage of HLA–B*1502 was associated with 100–fold greater risk of developing SJS/TEN with CBZ in Asians whilst carriage of HLA–A*3101 in Europeans, Japanese and Koreans was associated with 10–fold greater risk of developing all hypersensitivity reactions to CBZ. The BNSU for severe hypersensitivity to AEDs was setup to raise awareness of AED–induced severe hypersensitivity reactions amongst neurologists and increase recruitment of these patients to the molecular genetics of adverse drug reaction study at the University of Liverpool. The aim of the molecular genetics of hypersensitivity study is to validate previously reported genetic associations and identify new genetic associations in drug hypersensitivity. This will allow development of genetic tests that can inform drug choice enabling clinicians to optimise efficacy and minimise the side–effects to AED treatment in future. Potential patients identified by the BNSU for hypersensitivity to AEDs will be consented and asked to provide a sample of venous blood or saliva for extraction and storage of DNA. Clinical details about the hypersensitivity reaction will then be completed by the neurology team caring for the patient. The BNSU for severe hypersensitivity to AEDs started in August 2011. Since then 14 neurologists have used the system and 16 cases have been reported. Case descriptions were provided for 12 of these cases. Lamotrigine was the most frequently reported AED and associated with six cases of hypersensitivity. This was followed by carbamazepine which was the culprit drug in five cases of hypersensitivity and phenytoin responsible for one hypersensitivity reaction. SJS/TEN was suspected or diagnosed in seven patients. Four patients had a suspected diagnosis of HSS and an unknown reaction was recorded in one patient. Following analysis of these case descriptions ten patients were suitable for recruitment to the molecular genetics of adverse drug reaction study. One of these patients has been recruited and their DNA stored whilst the other nine patients are awaiting R&D approval at their NHS Trusts. The BNSU for hypersensitivity to AEDs has been successful over the first 18 months and identified ten patients who have suffered with severe hypersensitivity to AED therapy. National recruitment schemes such as the BNSU are important because they enable clinicians and researchers to recruit large numbers of patients for rare conditions such as severe hypersensitivity reactions to AEDs. Without these coordinated national schemes genetic association studies would not have sample sizes large enough to provide adequate power to detect significant genetic associations.